P150 Predictive value of SIRS severity index on survival in elderly women (≥70 years) with advanced epithelial ovarian cancer. (1st November 2019) - Song, YJ; Todd, SL; Xiong, Y; Wenham, R; Extermann, M; Chon, HS
Abstract : Introduction/Background: This study assessed the predictive value of age and Cumulative Illness Rating Scale (SIRS) severity index on the management of advanced stage epithelial ovarian cancer (EOC) patients aged 70 years or older. Methodology: A retrospective chart review was performed in elderly women (>70years) with advanced EOC cancer at a Moffitt Cancer Center between January 2007 and April 2016. Exclusion criteria included non-epithelial histology, stage less than IIIC, low grade or incomplete medical records. Clinical data were analyzed according to the following age group categories: (1) group 1: 70 to 74 years versus (2) group 2: 75 to 79 years versus (3) group 3: older than 79 years. Results: One hundred twenty seven patients were identified (66 in age group 1, 35 in group 2, and 26 in group 3). There was no difference concerning clinicopathologic data between 3 age groups. Optimal debulking rate (77.2% in age group 1, 82.8% in group 2, and 76.9% in group 3, p=0.78) and completeness of adjuvant chemotherapy (80.3% in age group 1, 82.8% in group 2, and 65.3% in group 3, p=0.21) were similar in these groups. The rate of using G-CSF during chemotherapy were not different between age group. Multivariate analyses confirm that only the pretreatment assessment of SIRS severity index was an independent prognostic factor for OS in elderly women (>70years) with advanced EOC (HR0.52, p=0.02). Older age was not associated with decreased OS in this cohort Conclusion: High CIRS severity index could be a predictor of poor survival in elderly women (>70years) with advanced EOC. Disclosure: Nothing to disclose.